2023
DOI: 10.3390/foods12173244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Encapsulation Techniques on Aroma Retention of Pistacia terebinthus L. Fruit Oil: Spray Drying, Spray Freeze Drying, and Freeze Drying

Delal Meryem Yaman,
Derya Koçak Yanık,
Aysel Elik Demir
et al.

Abstract: The primary aim of this investigation was to assess the impact of varying the ratio of gum arabic to maltodextrin and employing diverse encapsulation techniques on the properties of the powdered substance and the capacity to retain the aromatic attributes of terebinth fruit oil. Distinct ratios of gum arabic to maltodextrin (75:25, 50:50, and 25:75) were employed to fabricate oil-in-water emulsions. The utmost stability of the emulsion was realized at a gum arabic to maltodextrin ratio of 75:25, characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Rajkumar et al (2020) reported that the spray-dried product retained more volatiles than the one produced by the most commonly used hot air-dried method in dehydrated tomatoes. It was reported that optimized spray-dried Pistacia terebinthus L. had higher aroma retention compared to freeze-dried samples . It is worth noting that the aroma of ginger is a complex matrix that includes volatile components of multiple chemical groups such as terpenes, alcohols, aldehydes, acids, lactones, ketones, and phenols .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajkumar et al (2020) reported that the spray-dried product retained more volatiles than the one produced by the most commonly used hot air-dried method in dehydrated tomatoes. It was reported that optimized spray-dried Pistacia terebinthus L. had higher aroma retention compared to freeze-dried samples . It is worth noting that the aroma of ginger is a complex matrix that includes volatile components of multiple chemical groups such as terpenes, alcohols, aldehydes, acids, lactones, ketones, and phenols .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that optimized spray-dried Pistacia terebinthus L. had higher aroma retention compared to freeze-dried samples. 12 It is worth noting that the aroma of ginger is a complex matrix that includes volatile components of multiple chemical groups such as terpenes, alcohols, aldehydes, acids, lactones, ketones, and phenols. 13 The aroma changes of these compounds can be influenced by physical evaporation, chemical degradation, and dynamic chemical transformations among various aroma compounds in ginger.…”
Section: ■ Introductionmentioning
confidence: 99%